2008
DOI: 10.1261/rna.761708
|View full text |Cite
|
Sign up to set email alerts
|

A novel sequence-specific RNA quantification method using nicking endonuclease, dual-labeled fluorescent DNA probe, and conformation-interchangeable oligo-DNA

Abstract: We have developed a novel, single-step, isothermal, signal-amplified, and sequence-specific RNA quantification method (Lassay). The L-assay consists of nicking endonuclease, a dual-labeled fluorescent DNA probe (DL-probe), and conformationinterchangeable oligo-DNA (L-DNA). This signal-amplified assay can quantify target RNA concentration in a sequence-specific manner with a coefficient of variation (Cv) of 5% and a lower limit of detection of 0.1 nM. Moreover, this assay allows quantification of target RNA eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The opening of the probe exposes a sequence complementary to a quenched fluorescent probe with a 5′-fluorophore and a 3′-quencher. Annealing with the quenched probe generates a ds-BbvCI site such that Nb.BbvCI nicks the strand containing quenched fluorescent probe and releases the fluorophore from being quenched ( 114 ). This RNA detection scheme has been shown to be quantitative and not requiring purification of the RNA, and should be applicable to the detection of ss DNA.…”
Section: Application Of Neasesmentioning
confidence: 99%
“…The opening of the probe exposes a sequence complementary to a quenched fluorescent probe with a 5′-fluorophore and a 3′-quencher. Annealing with the quenched probe generates a ds-BbvCI site such that Nb.BbvCI nicks the strand containing quenched fluorescent probe and releases the fluorophore from being quenched ( 114 ). This RNA detection scheme has been shown to be quantitative and not requiring purification of the RNA, and should be applicable to the detection of ss DNA.…”
Section: Application Of Neasesmentioning
confidence: 99%
“…NEs themselves nowadays are widely used, e.g. for DNA amplification [8], in sequencing procedures [9], for DNA [10] or RNA detection and quantification [11]. To improve the existing methods and to develop new approaches, it is necessary to acquire information about the mechanism of NE action.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel nucleic acid detection technique called nicking endonuclease enhanced signal amplification (NESA) has been reported by Kiesling et al 12 As a new nucleic acid detection technique, NESA has been reported to have distinct specificity for the detection of a single-base mismatch. However, the sensitivity of previously reported NESA was not high enough (only in the picomolar level), even when molecular beacons, 13 a dual-labeled fluorescent DNA probe, 14 or nanoparticles 15 were used to increase the sensitivity. Furthermore, the NESA-based DNA detection methods previously reported have other limitations such as complexity of fabrication and are time consuming.…”
mentioning
confidence: 87%